CORELATION USE OF HORMONAL CONTRACEPTION WITH INCIDENCE BREAST CANCER IN SURGERY POLICLINIC RSUD JOMBANG - Mudhawaroh Mudhawaroh; Septi Fitrah Ningtyas; Putu Arik Herliawati (Jambura Journal of Health Sciences and Research, 2022)
The number of cases of breast cancer in the world ranks second only to cervical cancer, breast cancer in addition to be one of the major killer of women in the world and the tendency of increase in cases in the world or in Indonesia. The purpose of this study was to determine the relationship between the use of hormonal contraception with the incidence of breast cancer in the surgical hospital poly Jombang. This study uses a method of analysis with case control design. The case group was women with breast cancer in Poly Surgical Hospital Jombang and control group was women who did not have breast cancer in Poly Surgical Hospital Jombang, where each - each sample was 31 respondents. Odds Ratio value is calculated using a 2 x 2 table and the p-value using chi square test using SPSS. There were 31 respondents 31 respondents case and control groups in this study. Having calculated by multivariate logistic regression analysis showed that there was no significant association between the use of hormonal contraception with the incidence of breast cancer in Jombang Poly Surgical Hospital, which is characterized by the value of p = 0.276 and the value of OR = 8.523 Incompatibility results of this study with previous research or theory that there is possible to have several possibilities. This can occur when women who use hormonal contraceptives maintain a healthy lifestyle, by maintaining the diet and activity by diligently exercising and minimizing the consumption of fatty foods, which in this study is supported by the nutritional status of women with breast cancer in part great rmempunyai normal nutritional status. However, if the user in the long term will also affect the incidence of breast cancer.